Does compulsory schooling affect health? Evidence from ambulatory claims data - Tatjana Begerow; Hendrik Jürges (The European Journal of Health Economics, 2021)
Using claims data on more than 23 million statutorily insured, we investigate the causal effect of schooling on health in the largest and most comprehensive analysis for Germany to date. In a regression discontinuity approach, we exploit changes in compulsory schooling in West Germany to estimate the reduced form effect of the reforms on health, measured by doctor diagnoses in ICD-10 format covering physical as well as mental health conditions. To mitigate the problem that empirical results depend on subjective decisions made by the researcher, we perform specification curve analyses to assess the robustness of findings across various model specifications. We find that the reforms have, at best, very small impacts on the examined doctor diagnoses. In most of the specifications we estimate insignificant effects that are close to zero and often of the “wrong” sign. Therefore, our study questions the presence of the large positive effects of education on health that are found in the previous literature.
Keywords: I14; I24; I26; 610; Compulsory schooling laws; Doctor-diagnosed health conditions; Regression discontinuity design; Causality